Membangun Integritas Aparatur Negara melalui Etika Pancasila dalam Birokrasi - Annisa Nur Fadhillah; Aisyah Nanda Salsabila; Rayzah Arsondatra Perdana Syahputra; Moh. Faizin (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2025)
Abstract The poor integrity of state officials within the bureaucracy remains a persistent issue every year. Corruption and online gambling are the main issues affecting state officials who lack a sense of responsibility and are blind to the suffering of the Indonesian people. This article will attempt to provide a solution to the problem of state official integrity within the bureaucracy. The research aims to analyze and explain the causes of poor integrity and solutions to build state official integrity through Pancasila ethics within the bureaucracy. The research method used is qualitative research, namely literature and documentation studies that focus on the causes and solutions to the problem of state official integrity within the bureaucracy through Pancasila ethics. Honest and responsible behavior, a strict oversight system, and proper state official management are the results of this research that will build and strengthen state official integrity within the bureaucratic system. The ethical values ​​of Pancasila serve as a strong foundation for building state official integrity that prioritizes the interests of the public. Pancasila can maintain public trust through integrity and professional service.